Contalactone, a contaminant formed during chemical synthesis of the strigolactone reference GR24 is also a strigolactone mimic. (December 2019) - de Saint Germain, Alexandre; Retailleau, Pascal; Norsikian, Stéphanie; Servajean, Vincent; Pelissier, Franck; Steinmetz, Vincent; Pillot, Jean-Paul; Rochange, Soizic; Pouvreau, Jean-Bernard; Boyer, François-Didier
Abstract: Strigolactone (SL) plant hormones control plant architecture and are key players in both symbiotic and parasitic interactions. GR24, a synthetic SL analog, is the worldwide reference compound used in all bioassays for investigating the role of SLs in plant development and in rhizospheric interactions. In 2012, the first characterization of the SL receptor reported the detection of an unknown compound after incubation of GR24 samples with the SL receptor. We reveal here the origin of this compound (P270), which comes from a by-product formed during GR24 chemical synthesis. We present the identification of this by-product, named contalactone. A proposed chemical pathway for its formation is provided as well as an evaluation of its bioactivity on pea, Arabidopsis, root parasitic plant seeds and AM fungi, characterizing it as a SL mimic. Quality of GR24 samples can be easily checked by carrying out microscale hydrolysis in a basic aqueous medium to easily detect P270 as indicator of the presence of the contalactone impurity. In all cases, before being used for bioassays, GR24 must be careful purified by preparative HPLC. Graphical abstract: Image 1 Highlights: Characterization of (±)-contalactone, a contaminant of synthetic strigolactone GR24. (±)-Contalactone inhibits branching in pea via RMS3/PsD14 strigolactone receptor. (±)-Contalactone represses hypocotyl elongation in Arabidopsis via AtD14 and AtKAI2. (±)-Contalactone is a potent germination stimulant of various root parasitic plants. (±)-Contalactone induces the colonization of AM fungi in Medicago truncatula .